Faults Detection in Three Phase Transmission Line with Safety Measure - Monu; Piyush; Rishi Sharma; Vipin Kumar Ahuja (International Journal of Engineering and Management Research, 2023)
The "Faults Detection In Three Phase Transmission Line With Safety Measure" aims to enhance the safety and reliability of electrical power transmission systems by developing an intelligent fault detection and monitoring system for transmission lines. The project utilizes advanced sensing and communication technologies to detect faults on transmission lines promptly and accurately, allowing for timely intervention and mitigation of potential hazards. The proposed Transmission Line Fault Safety Project contributes to enhancing the reliability and safety of transmission line operations. By enabling rapid fault detection, early warning systems, and effective response mechanisms, it aims to reduce downtime, prevent accidents, and improve the overall efficiency of electrical power transmission systems.